KONFLIK SEMU ANTARA LOGIKA DAN AGAMA DALAM PENDIDIKAN ISLAM STUDY PUSTAKA ATAS KARYA AL GHAZALI DAN IBNU RUSYD - Rudhi; Tahir, Muh. Sakti; Djayadin, Chairunnisa; Lamiada, Muh Akbar (Jurnal Al-Mubarak: Jurnal Kajian Al-Qur'an dan Tafsir, 2025)
The conflict between logic and religion is often considered a polemic that hinders the development of Islamic thought. However, this study finds that the dispute between Al-Ghazali and Ibn Rushd regarding logic and religion is more of a superficial conflict, rather than a substantial disagreement. This literature review analyzes the major works of both figures, such as Tahafut al-Falasifah (Al-Ghazali) and Tahafut al-Tahafut (Ibn Rushd), to explore their contributions to Islamic education. The results show that their differences actually provide an opportunity for the integration of religious knowledge, philosophy, and logic into the Islamic education curriculum. Thus, contemporary Islamic education needs to be integrative and adaptive to face the challenges of the times.